Comparison of the behaviour of steel, pure FRP and hybrid shear walls under cyclic seismic loading in aspect of stiffness degradation and energy absorption. (20th March 2018) - Petkune, Natalja; Donchev, Ted; Hadavinia, Homayoun; Wertheim, David; Limbachiya, Mukesh
Highlights: Hybrid and pure FRP shear walls have improved behaviour under seismic loading. Pure FRP shear walls have excellent load capacity and resistant to stiffness loss. FRP shear walls have good energy absorption and potential for increased durability. Abstract: Introducing of light-weight lateral load resisting systems, such as steel shear walls (SSW) is very beneficial for multi-storey buildings. Further improvement of such elements via introducing fibre reinforced polymer (FRP) materials is expected to allow increasing of their ultimate load capacity, stiffness and energy absorption. The aim of presented research is to compare the behaviour of modified SSW via inclusion of FRP in infill plate design. Produced and tested shear wall specimens are three different types: with steel infill plate (control), with FRP infill plate and with hybrid steel/FRP infill plate. All samples are loaded under quasi-static cyclic seismic loading as defined in ATC-24 protocol. The highest ultimate load capacity and lowest stiffness degradation is achieved for sample with glass FRP infill plate, followed by hybrid (carbon FRP/steel and glass FRP/steel) specimens. Highest cumulative energy absorption for predominant part of the investigated amplitudes was achieved for hybrid specimens. The obtained results indicate that the innovative shear walls with FRP and hybrid infill plates offer excellent load carrying capacity and energy absorption, relatively small loss of stiffness and potential for increased durability in comparison with conventional SSW systems.